Household disability and time preferences: Evidence from incentivized experiments in Vietnam - Ute Rink; Theresa Rollwage (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2022)
This paper investigates individual time preferences between individuals living in a disability household and those who live in a non-disability household in Vietnam. Using randomized primes together with experimental tasks to elicit time preferences, our empirical results show that individuals living in a disability household are (i) more likely to be present biased, and (ii) more patient. The effects are even more pronounced when the disability happened recently (within the last 8 years). These findings show causal evidence that time preferences differ among more vulnerable groups of society and may be one cause for their often observed adverse socioeconomic conditions.
Keywords: D01; D91; I14; 330; Disability; Time preferences; Priming; Vietnam